Irrigation and water policies in the Mekong region: current discourses and practices - Molle, Francois (International Water Management Institute, 2005)
This report documents current irrigation and water policies in the Mekong countries. It successively reviews planning issues, water policies and legal frameworks, the setting up of water policy "apex bodies," participatory policies, and IWRM/river basin management.